Análise do processo de desenvolvimento da autonomia dos alunos da educação a distância no Instituto Federal do Amapá – Campus Santana - CASTRO, Giliane Nazaré Videira (2021)
Distance Education (EaD) is a teaching modality in which the student is the protagonist of their learning, so it is necessary that they have an autonomous profile to manage their studies. The lack of student autonomy represents a problem for the educational process, as it compromises learning and can contribute to evasion in courses offered in this modality. Given this perspective, this research addressed the theme of autonomy of the EaD student having as guiding questions: do students of subsequent courses in the EaD modality offered by IFAP - Campus Santana have the level of autonomy necessary for the educational process?How much does the institution adopt methodological strategies and institutional tools aimed at motivating the autonomy of students in distance learning courses? The general objective sought to analyze the process of developing the autonomy of students in subsequent courses, in the EaD modality, offered by IFAP - Campus Santana. Methodologically, the research is characterized as Applied, with a qualitative-quantitative approach, with an exploratory nature, adopting the Case Study. The locus was the IFAP – Campus Santana, where the semi-structured questionnaire was applied via Google Forms to 14 students and 6 teachers of the 3rd (last) module of the distance courses (Finance and Informatics). In interpreting the results, Content Analysis was used. The collected data were presented through graphs and the results were discussed in two analysis categories, A and B: Category A includes the analysis of the teachers' perceptions and Category B includes the analysis of the students' perceptions. As an integral part of this study, the Digital Booklet “Student autonomy in Distance Education” was prepared as an educational product, which was made available to students and subsequently evaluated by them. The results of this study demonstrate that teachers do not adopt methodological strategies that aim to motivate the construction of their students' autonomy, but rather teaching strategies. However, it is considered that they are insufficient, as most students do not have the necessary autonomy for this modality. In this sense, the educational product, the result of this study, presents itself as an institutional tool that will contribute to the motivation of students' autonomy.